Analisis Optimalisasi Hasil Perkebunan Teh Bahbutong PTPN IV Sidamanik Dengan Linear Programming - Ernida Siregar; Isnaini Harahap; Khairina Tambunan (Jurnal Manajemen Akuntansi (JUMSI), 2023)
The object of this study is the Tea Plantation Bahbutong PTPN IV Sidamanik.Sampling techniques in this study with interviews, observation and documentation.The Data used using secondary data is by using interviews, observation and documentation. Analytical techniques used in this study by using Linear Programming Test using Linear Programming with constraints, namely the cost of machinery, the cost of employee salaries, and the cost of raw materials. The results showed that bahbutong tea plantations have made careful planning in terms of production so that the use of Linear Programming method is not too influential in terms of production and based on the results of research production costs affect the income of bahbutong tea plantations. And based on the analysis of linear programming,it can be concluded that the bahbutong tea company has the maximum profit value from plantation production of Rp 638,787,500,000 in 2016-2023.